Specific skin changes induced by chemotherapy - Ding, Lin; Li, Qing-Jian; Wang, Ying; Bi, Zhuo-Fei; Chai, Jie; Jiang, Zhi-Min; Saw, Phei-Er; Hu, Hai; Yao, He-Rui (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Cancer remains the leading cause to death among Chinese populations, with increasing incidence and mortality every year. As we know, chemotherapy is the main systemic therapy for cancer patients, which frequently causes skin toxicity. Since this side effect is non-life threatening, the impact of its occurrence is often being neglected. However, skin toxicity does influence the quality of life of the patient and often leads to the decrease in dosage or even suspension of treatment, and therefore significantly altered the therapeutic outcome. Hereby, we first report four specific skin changes induced by chemotherapy which are observed in patients treated in our department (from March to October in 2015). To further establish our current observation, we reviewed pertinent publications regarding skin toxicity due to chemotherapy and summarized common skin toxicity induced by chemotherapy. Herein, by summarizing both common and rare skin adverse reactions induced by chemotherapeutic drugs, we hope to increase awareness in this area and possibly to come up with therapeutic interventions that could curb these side effects.